Design and Manufacture of a Mobile Electric Alembic for Naturally Occuring Essential Oils Extraction - Ravelomanantsoa H.; Ranaivoson S.L.O.; Razafindrakoto F.N.R.; Letsara R.; Razafindramanga A.W.; Rakotomamonjy P.; Razafimahefa M.V.; Koto-Te-Nyiwa Jean-Paul Ngbolua; Randriana N.R.F.; Robijaona Rahelivololoniaina B. (Budapest International Research in Exact Sciences (BirEx) Journal, 2023)
The present study concerns the design and manufacturing of a mobile electric alembic, for its use in the distillation of three essential oils (EOs). The design was based on thermodynamic and fluid mechanics calculations to establish the sizing of the device. The heating source used is electricity using electrical resistors.  Tests were carried out to verify the ability of the alembic to extract some essential oils (Eos) from aromatic plant, such as Cinnamomum camphora, Cymbopogon citratus, Corymbia citriodora. The EO yields obtained were comparable to those described in the AFNOR. The results of the Gas Chromatography analysis were similar to the published data.